Child Sacrifice in the Book of Leviticus: A Comparative Study with Ancient Near Eastern Practices - Tanasyah, Yusak; George, Alexi E. (MODERATE: Journal of Religious, Education, and Social, 2025)
Child sacrifice, a deeply disturbing yet widespread ritual in the Ancient Near East, represents one of the most striking contrasts between Israelite and pagan religious thought. This study explores the prohibition of child sacrifice in Leviticus 18:21 and 20:2–5 as a theological and ethical response to the death-centered cults surrounding ancient Israel. Employing a comparative-historical and exegetical approach, this research examines how the Levitical text redefines holiness, sacrifice, and divine justice within the wider Ancient Near Eastern context. The findings demonstrate that Leviticus transforms the logic of sacrifice from appeasement by destruction to covenantal communion grounded in life and obedience. This shift reveals a moral revolution in biblical theology—where holiness is not separation for privilege but participation in God’s life-giving justice. The study further argues that Leviticus’ rejection of Molech worship constitutes an enduring theological protest against all systems, ancient or modern, that exploit or destroy human life for ideological gain. Ultimately, Leviticus articulates a theology of life that unites divine worship with the protection of humanity, offering a prophetic vision profoundly relevant to today’s moral and technological world. Contribution:  This study contributes to biblical theology by demonstrating that Leviticus redefines the ancient logic of sacrifice into a moral theology of life, where holiness is expressed through justice, compassion, and the preservation of human dignity. It further offers a contemporary ethical framework that challenges modern societies to resist every form of dehumanizing ideology—the “modern Molechs”—by reaffirming the inseparable bond between divine worship and the sanctity of life.   Pengorbanan anak, sebuah ritual yang sangat mengerikan namun tersebar luas di wilayah Timur Dekat Kuno, merupakan salah satu kontras paling mencolok antara pemikiran religius bangsa Israel dan bangsa-bangsa kafir. Penelitian ini menelaah larangan terhadap pengorbanan anak dalam Imamat 18:21 dan 20:2–5 sebagai respons teologis dan etis terhadap kultus-kultus yang berpusat pada kematian di sekitar Israel kuno. Dengan menggunakan pendekatan komparatif-historis dan eksegetis, penelitian ini mengkaji bagaimana teks Imamat mendefinisikan ulang makna kekudusan, korban, dan keadilan ilahi dalam konteks luas dunia Timur Dekat Kuno. Hasil penelitian menunjukkan bahwa kitab Imamat mengubah logika pengorbanan dari penenangan melalui penghancuran menjadi persekutuan perjanjian yang berlandaskan pada kehidupan dan ketaatan. Perubahan ini mengungkapkan adanya revolusi moral dalam teologi biblika—di mana kekudusan tidak lagi berarti pemisahan demi keistimewaan, melainkan partisipasi dalam keadilan Allah yang memberi kehidupan. Penelitian ini juga berpendapat bahwa penolakan terhadap penyembahan Molekh dalam Imamat merupakan protes teologis yang abadi terhadap semua sistem—baik kuno maupun modern—yang mengeksploitasi atau menghancurkan kehidupan manusia demi keuntungan ideologis. Pada akhirnya, kitab Imamat menegaskan teologi kehidupan yang mempersatukan penyembahan kepada Allah dengan perlindungan terhadap kemanusiaan, menawarkan visi profetik yang sangat relevan bagi dunia moral dan teknologi masa kini. Kontribusi: Penelitian ini memperkaya teologi biblika dengan menafsirkan kitab Imamat sebagai transformasi dari logika korban kuno menjadi teologi moral kehidupan, di mana kekudusan terwujud dalam keadilan, belas kasih, dan penghormatan terhadap martabat manusia. Studi ini juga menawarkan kerangka etika modern yang menegaskan hubungan erat antara ibadah kepada Allah dan kesucian hidup sebagai perlawanan terhadap ideologi-ideologi yang mendehumanisasi.